A controlled approach to the emotional dilution of the Stroop effect. - Kathryn Fackrell (Public Library of Science (PLoS), 2013)
We re-examined a modified emotional Stroop task that included an additional colour-word alongside the emotional word, providing the response conflict of the traditional Stroop task. Negative emotionally salient (i.e. unpleasant') words are claimed to capture attention, producing a smaller Stroop effect for negative words compared to neutral words; this phenomenon is called the emotional dilution of the Stroop effect. To address previous limitations, this study compared negative words with lexically matched neutral words in a powered sample of 45 participants. Results demonstrated an emotional Stroop effect (slower colour-naming responses for negative words) and a traditional Stroop effect but not an emotional dilution of the Stroop effect. This finding is at odds with claims that other processing resources are diminished through the failure to disengage attention from emotional information. No matter how attention towards emotional information builds up over time, our findings indicate that attentional resources are not fully captured by negative words.